Generic strategies and financial performance persistence in the banking sector in Indonesia / Etikah Karyani and Hilda R. Rossieta - Karyani, Etikah; R. Rossieta, Hilda (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2018)
This study investigates the relationship between the bank strategic positioning and performance. A central question in the management literature has been to identify the sources of competitive advantage that allow firms to attain and persistent superior performance over their competitors. Bank can build competitive advantages by following either a cost leadership or a differentiation strategy. Bank adopting a cost leadership strategy principally attain advantages based on operational efficiency, and hence the performance of such firms should more persist over time than other bank adopting differentiation strategy. This study documents an empirical investigation of this premise using a sample of 216 firm-years over the period 2009-2013. This study details the development of constructs using audited financial-level archival data to capture a bank's strategic positioning. These constructs are then used in empirical models that explore the persistence of bank performance. Using confirmatory factor analysis, the results of these models estimation indicate that although both cost leadership and differentiation strategies have a positive effect on contemporaneous performance, only the efficiency strategy allows a bank to achieve and maintain superior performance in the future.